Adjunctive therapies and immunomodulating agents for severe influenza. (November 2013) - Hui, David S. C.; Lee, Nelson
Abstract : The value of adjunctive immunomodulatory therapies in treating severe influenza and other respiratory viral infections remains uncertain. Although often used, systemic corticosteroids may increase the risk of mortality and morbidity (e.g. secondary infections) in severe influenza and other viral infections, especially if there is delay or lack of effective antiviral therapy. Non‐randomized studies suggest that convalescent plasma appears useful as add‐on therapy for patients with severe acute respiratory syndrome, avian influenza A(H5N1), and influenza A (H1N1) 2009 pandemic [A(H1N1)pdm09), but it is limited by its availability. A recent randomized controlled trial (RCT) comparing hyperimmune globulin prepared from convalescent plasma against normal intravenous gammaglobulin (IVIG) manufactured before 2009 as control in patients with severe A(H1N1)pdm09 infection on standard antiviral treatment has shown that the hyperimmune globulin group who received treatment within 5 days of symptom onset had a lower viral load and reduced mortality compared with the controls. A number of agents with immunomodulatory effects (e.g. acute use of statins, N‐acetylcysteine, macrolides, PPAR agonists, IVIG, celecoxib, mesalazine) have been proposed for influenza management. However, more animal and detailed human observational studies and preferably RCTs controlling for the effects of antiviral therapy and disease severity are needed for evaluating these agents. The role of plasmapheresis and hemoperfusion as rescue therapy also merits more investigation.